Pengalaman adolescent mother dalam memberikan ASI eksklusif - Reni Purwo Aniarti (MEDIA ILMU KESEHATAN, 2022)
Background: Breastfeeding provides the optimal nutrition for babies. Neonatal morbidity and mortality could be reduced by mothers's important role in delivering exclusive breastfeeding to infants aged 0 to 6 months. The knowledge of an adolescent mothers when breastfeeding can effect the mothers's mental and physical wellness.Objective: This study investigated the exclusive breastfeeding experiences of adolescents mothers.Methods: Exploring the meanings and experiences of adolescent mothers via in-depth interviews focusing on life experience as a way of describing the phenomenological approach.Results: There were seven participants and seven themes in this study. The seven themes include 1) Adolescent mothers's experience in giving exclusive breastfeeding, 2) Adolescent mothers's decision to give exclusive breastfeeding, 3) Adolescent mothers's difficulties in giving exclusive breastfeeding, 4) Problems and obstacles in giving exclusive breastfeeding, 5) Adolescent mothers to survive in exclusive breastfeeding, 6) Adolescent mothers in increasing the volume of breast milk, 7) The motivation of adolescent mothers to give exclusive breastfeeding.Conclusion: Adolescent mothers provide supplemental nutrition for breastfed infants until the age of six months. The importance of family support and health professionals in mothers's awareness of exclusive breastfeeding.